History of Maternal Fetal Loss and Childhood Leukaemia Risk in Subsequent Offspring: Differentials by Miscarriage or Stillbirth History and Disease Subtype. Issue 5 (14th July 2015) - Karalexi, M. A.; Skalkidou, A.; Thomopoulos, T. P.; Belechri, M.; Biniaris‐Georgallis, S.‐I.; Bouka, E.; Baka, M.; Hatzipantelis, E.; Kourti, M.; Polychronopoulou, S.; Sidi, V.; Stiakaki, E.; et al.
Abstract Background Despite the putative intrauterine origins of childhood (0–14 years) leukaemia, it is complex to assess the impact of perinatal factors on disease onset. Results on the association of maternal history of fetal loss (miscarriage/stillbirth) with specific disease subtypes in the subsequent offspring are in conflict. We sought to investigate whether miscarriage and stillbirth may have different impacts on the risk of acute lymphoblastic leukaemia (ALL) and of its main immunophenotypes (B‐cell and T‐cell ALL), as contrasted to acute myeloid leukaemia (AML). Methods One thousand ninety‐nine ALL incidents (957 B‐ALL) and 131 AML cases along with 1:1 age and gender‐matched controls derived from the Nationwide Registry for Childhood Hematological Malignancies and Brain Tumors (1996–2013) were studied. Multivariable regression models were used to assess the roles of previous miscarriage(s) and stillbirth(s) on ALL (overall, B‐, T‐ALL) and AML, controlling for potential confounders. Results Statistically significant exposure and disease subtype‐specific associations of previous miscarriage(s) exclusively with AML [odds ratio (OR) 1.67, 95% confidence interval (CI) 1.00, 2.81] and stillbirth(s) with ALL [OR 4.82, 95% CI 1.63, 14.24] and B‐ALL particularly, emerged. Conclusion Differential pathophysiological pathways pertaining to genetic polymorphisms or cytogenetic aberrations are likely to create hostile environments leading either to fetal loss or the development of specific leukaemia subtypes in subsequent offspring, notably distinct associations of maternal miscarriage history confined to AML and stillbirth history confined to ALL (specifically B‐ALL). If confirmed and further supported by studies revealing underlying mechanisms, these results may shed light on the divergent leukemogenesis processes.